Adequate Fertilization, Application Method and Sowing Techniques Improve Maize Yield and Related Traits. Issue 19 (28th October 2021) - , Imran; , Amanullah; Ali khan, Asad; Mahmood, Tariq; Al Tawaha, Abdel Rahman; Khanum, Samia
ABSTRACT: Determining optimum plant populations with improved planting methods and adequate fertilization with soil modification possesses a gigantic potential to enhance maize productivity. Experiments were performed on a farmer's field in the framework of Farmers' Field School during the Kharif season of 2014. The experiment design was RCB, with split plot arrangements having three replications. Three sowing techniques [drill sowing (DS), dibbling sowing (DBS), and ridge sowing (RS)], three organic nitrogen (N) sources and two application methods were studied during the experiment. Sowing techniques were allocated to the main plots, while nitrogen sources, cattle manure (CM), urea and Chicken manure (ChM) and its methods of application (before and after tilling) along with control were allocated to the sub-plots. The results showed that the sowing methods and the treatment of nitrogen had significant effects on maize productivity. Comparing the different sowing methods, RS has a higher biological yield (12%), grain yield (38%) than DBS. A higher number of grain ear −1 (32%), 1000 grain weight (11%), grain yield (52%), biological yield (28%), and harvest index (18%) were observed with plots treated with ChM than control plots. Similarly, higher grain ear −1 (6%), 1000 grain weight (7%), grain yield (32%), biological yield (17%), and harvest index (10%) were observed with N application before tilling than after tilling application method. With before tilling of ChM, maize yield was higher than the CM and Urea. In conclusion, ChM and CM embedded in soil with RS can sustainably increase maize yield and soil productivity.